Rancang Bangun Reflektor Cahaya Matahari Dengan Cermin Datar Berbasis Mikrokontroler Untuk Alat Solar Pasif Desalinasi - Pell, Yeremias M.; BOYMAU, MAIKEL WAHYUDI; Tarigan, Ben V. (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2022)
The research has been conducted on design solar light reflector with flat mirror based on microcontroller for passive solar desalination device. The purpose of this research is to design solar light reflector using flat mirror based on microcontroller for passive solar desalination device that can function properly so that it can be used by coastal communities who need fresh water. The method used in this research is design. This research was started by design the reflector and reflector frame, design the servo mount, design the connecting arm and testing using sea water. The results showed the design of microcontroller-based solar reflector device for desalination equipment with dimensions of 60 cm long, 30 cm wide, and 55 cm high with drive system using Arduino UNO and driving motor using 25 kg DS3225 servo motor and with three reflector opening angles of 30⁰, 45⁰ and 60⁰ which move automatically every 2 hour and the production of fresh water produced in the 6 hour desalination process is 940 ml.